Peran Burnout dalam Memediasi Pengaruh Gaya Kepemimpinan Digital terhadap Turnover Intention Karyawan CV XYZ Karanganyar - Aprilia Eka Lativa; Agus Suyatno; Khabib Alia Akhmad; Umi Hanifah (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2026)
A digital leadership style does not automatically lower turnover intention, since burnout can still emerge among staff. This study examines the effect of digital leadership style on turnover intention, with burnout as a mediating variable among employees at CV XYZ Karanganyar. The design is explanatory with a quantitative approach. Data were collected via a Likert-scale questionnaire distributed to 77 employees selected through simple random sampling, then analyzed using SEM-PLS with SmartPLS 4.1. Findings show that digital leadership style has no significant direct effect on turnover intention, but has a negative and significant effect on burnout. Burnout, in turn, has a positive and significant effect on turnover intention and fully mediates the effect of digital leadership style on turnover intention in a negative and significant direction. Theoretically, the findings extend job demands-resources and social exchange theory via burnout's mediating role; practically, they suggest firms should manage burnout alongside strengthening digital leadership.